Cost of Disease Progression in Patients with Metastatic Breast, Lung, and Colorectal Cancer. (22nd February 2019) - Reyes, Carolina; Engel‐Nitz, Nicole M.; DaCosta Byfield, Stacey; Ravelo, Arliene; Ogale, Sarika; Bancroft, Tim; Anderson, Amy; Chen, May; Matasar, Matthew
Abstract: Introduction: To reduce health care costs and improve care, payers and physician groups are piloting value‐based and episodic or bundled‐care payment models in oncology. Disease progression and associated costs may affect these models, particularly if such programs do not account for disease severity and progression risk across patient populations. This study estimated the incremental cost of disease progression in patients diagnosed with metastatic breast cancer (mBC), colorectal cancer (mCRC) and lung cancer (mLC) and compared costs among patients with and without progression. Methods: This was a retrospective study using U.S. administrative claims data from commercial and Medicare Advantage health care enrollees with evidence of mBC, mCRC, and mLC and systemic antineoplastic agent use from July 1, 2006, to August 31, 2014. Outcome measures included disease progression, 12‐month health care costs, and 3‐year cumulative predictive health care costs. Results: Of 5, 709 patients with mBC, 3, 707 patients with mCRC, and 5, 201 patients with mLC, 56.8% of patients with mBC, 58.1% of those with mCRC, and 80.3% of those with mLC patients had evidence of disease progression over 12 months. Among patients with mBC and mCRC, adjusted and unadjusted health care costs were significantly higher among progressors versus nonprogressors. Per‐patient‐per‐month costs, which accounted for variable follow‐up time, were almost twice as high among progressors versus nonprogressors in patients with mBC, mCRC, and mLC. In each of the three cancer types, delays in progression were associated with lower health care costs. Conclusion: Progression of mLC, mBC, and mCRC was associated with higher health care costs over a 12‐month period. Delayed cancer progression was associated with substantial cost reductions in patients with each of the three cancer types. Implications for Practice: Data on the rates and incremental health care costs of disease progression in patients with solid tumor cancers are lacking. This study estimated the incremental costs of disease progression in patients diagnosed with lung cancer, breast cancer, and colorectal cancer and compared health care costs in patients with and without evidence of disease progression in a real‐world population. The data obtained in our study quantify the economic value of delaying or preventing disease progression and may inform payers and physician groups about value‐based payment programs. Abstract : To improve care coordination and cost‐effectiveness of cancer care, payers and physicians are transitioning from traditional fee‐for‐service payment systems to value‐based and bundled‐care models in oncology. This article provides estimates of the incremental cost of disease progression in patients with cancer and compares costs among patients with and without evidence of disease progression. Quantifying the financial impact of progression of disease can inform decisions about participating in or setting up episode/bundled payment programs.